Clinical profiling of right ventricular infarction in patients with acute inferior wall myocardial infarction - Khandait, Vinod; Sarwale, Suresh; Atkar, Chandrashekhar; Khandait, Harshwardhan (International Journal of Advances in Medicine, 2019)
Background: Incidence of Right Ventricular Myocardial Infarction (RVMI) associated with Inferior Wall Myocardial Infarction (IWMI) is reported to be quite high (30%-50%). To diagnose coexisting RVMI is important, since its early recognition and proper treatment reduces overall morbidity and mortality in IWMI. Author assessed the incidence and clinically profiled patients with right ventricular infarction in acute inferior wall myocardial infarction and analysed the effects of RVMI on clinical outcome of IWMI. Methods: A total of 150 patients of IWMI were evaluated in the present hospital based prospective observational study over duration of two years. They were evaluated for coronary risk factors like diabetes mellitus, hypertension, smoking, obesity, alcohol and dyslipidemia. Twelve-lead ECG, cardiac enzyme assay and echocardiography were undertaken in all the participants. Results: Of the total 150 patients, 45 (30%) patients had right ventricular myocardial infarction (RVMI). Complications were significantly lower in patients with isolated IWMI as compared to patients with IWMI and associated RVMI except pulmonary edema (p<0.05). Of the total 22 (14.67%) deaths in the present study, 18 (12%) had associated RVMI and 4 (2.66%) isolated IWMI, the difference being statistically significant. Conclusions: Involvement of right ventricle increases rate of complications as well as the mortality rate in patients with inferior wall myocardial infarction.